Histopathological Assessment of Fusarium pseudograminearum Colonization of Cereal Culms During Crown Rot Infections - Knight, Noel L; Sutherland, Mark W (Plant disease, 2016)
Histopathological assessment of the crown rot pathogen Fusarium pseudograminearum was performed using fluorescence microscopy of culm tissues of six cereal genotypes grown in inoculated field conditions. Tissue samples were collected at 10, 16, and 22 weeks after planting (WAP). Colonization of culm tissues was initiated through epidermal penetration, most distinctly through stomatal apertures, and progressed into the parenchymatous hypoderm, which exhibited the discoloration used as the basis for visual assessment of disease. Hyphae spread from the culm base vertically through the tissues, initially via the hypoderm and pith cavity. Colonization of sclerified cells occurred later in the disease process. Both xylem and phloem tissues became colonized by 16 WAP in all host genotypes, with colonization being less extensive in the more resistant genotypes. Culms displaying dead head symptoms revealed dense colonization in at least the first three internodes, with frequent xylem vessel and phloem cell occlusions. Paired living culms from the same plants exhibited less extensive colonization. These observations have revealed the ability of F. pseudograminearum to colonize all cell types of nodal and internodal sections, including vascular tissues, across all host genotypes. This study is the first detailed examination of the pattern of F. pseudograminearum colonization in adult hosts and indicates a potential vascular mechanism by which the effects of crown rot are produced.